Uso de descritores químico-quânticos como etapa de pós-processamento do protocolo de redesenho de enzimas - Farias, Wenison Marrone Souza (2022)
In a constant search for the reduction of energy consumed, the use of catalysts has developed a lot, among which enzymes are the ones that have the highest performance in a homogeneous environment. In search of these catalysts for industrial reactions, a wide range of theoretical studies focused on enzyme development have been developed, such as the Rosetta enzymatic design protocol, which promotes mutations in protein structures and seeks to create or improve the reactions that it catalyzes. In this study, we try to improve this protocol, presenting improvements in the selection of probable structures with catalytic capacity and thus propose an additional step to the design protocol based on the post-processing of the enzymesubstrate complex by the use of enzyme-binding enthalpy (ΔHbinding) and reactivity descriptors. Thus, we developed a method that comprises using the structures designed by Rosetta and re-ranking them by performing quantum chemical calculations of ΔHbinding through the semiempirical Hamiltonian PM7 considering solation effect (COSMO model) and the MOZYME algorithm. Additionally, from the wave function of the enzymes, reactivity descriptors were calculated by using the frozen orbitals approximation considering molecular orbitals near gap HOMO-LUMO as a band, BD, or calculating its weighted formulation, EW. To validate this method, we sought the literature, structures designed by Rosetta with their kinetic characterization performed. As a result, by using the calculation of ΔHbinding, it was possible to improve the ranking, previously ranked by rosetta’s score. Thus improving for elimination reaction of Kemp 17 positions and for the reaction of Diels-Alder leaving in the top 10 places. Regarding the reactivity descriptors, for the reaction of Kemp, it was possible to observe that the change of only one residue in the supleKEstructure59 in relation to the structure that presented the highest catalytic capacity, nativeKE59, caused the NAS property to move away from the ligand, thus indicating the catalytic inactivity of the supleKE structure59. Therefore, the combination of these two approaches contributed to the ranking of better structures and, among them, aided to select those that have their NAS and EAS quantities located at the enzymes’ active site.